Method for modifying battery carbon-sulfur positive electrode material by using defect-free original graphene

Through defect-free original graphene coating and nanocarbon secondary coating technology, graphene-modified carbon-coated sulfur composite cathode material is formed, which solves the electrical conductivity, thermal conductivity and cycle life of the elemental sulfur cathode material, and realizes the High-performance carbon-sulfur composite cathode material.

CN119447261APending Publication Date: 2025-02-14CHENGDU DAAISBEICENE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680608.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Due to the defects such as poor electrical conductivity, poor thermal conductivity, large volume expansion rate and low cycle life, it is difficult to achieve large-scale market application.

Method used

Defect-free original graphene is used for primary coating, and then through nanocarbon secondary coating technology, a graphene-modified carbon-coated sulfur composite positive electrode material is formed to block ions from embedded in the sulfur lattice, and solve the sulfur expansion rate and cycle life. The problem.

Benefits of technology

It significantly improves the electrical conductivity, thermal conductivity, mechanical strength and reversible energy density of the material, reduces the sulfur expansion rate, extends the cycle life, and realizes a high-performance carbon-sulfur composite cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of a battery positive electrode material, in particular to a method for modifying a battery carbon-sulfur positive electrode material by using defect-free original graphene, which comprises primary coating, secondary coating and post-treatment. According to the method, defect-free original graphene coating modification is carried out on a carbon-sulfur positive electrode material of a liquid / solid lithium-sulfur battery, and ion intercalation lattice induced blocking of sulfur is completed through a nanocarbon secondary coating technology. Compared with the existing sulfur / sulfur-carbon positive electrode material, the specific capacity of the graphene sulfur-carbon positive electrode material prepared by the method disclosed by the invention is greatly increased and is close to a theoretical value, and the electrical conductivity and the heat-conducting property are greatly improved. The weight energy density and the volume density of the liquid / solid lithium-sulfur battery prepared by using the composite material are remarkably increased, the safety, the reliability and the like are far superior to those of the current lithium-sulfur battery of the same type, the operation of a battery management system is very facilitated, and the charge-discharge cycle index and the service life are remarkably improved. The method is simple to operate, convenient to prepare, short in production period and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery positive electrode material preparation, and in particular to a method for modifying a battery carbon-sulfur positive electrode material by using defect-free original graphene. Background Art

[0002] At present, due to considerations of energy density, economy, safety and recyclability, 90% of the current mainstream kinetic battery cathode materials are lithium iron phosphate / ternary lithium cathode materials, and the energy density of the battery cell has reached 250Wh / kg (theoretical specific capacity is 200mAh / g). In the future, the design and exploration of lithium iron phosphate / ternary lithium material systems will further increase their energy density, which is expected to reach 300Wh / kg - 330Wh / kg, when the energy density will reach its "ceiling". However, the market is very demanding. The market's expectations for power batteries are currently 350-400Wh / kg, and will reach more than 500Wh / kg in the next decade. The current lithium iron phosphate / ternary lithium material system can no longer meet this requirement.

[0003] People have found that sulfur has great advantages as a positive electrode material. Its theoretical specific capacity is 1675mAh / g, the potential difference is as high as 5V, and the theoretical energy density is as high as 2700Wh / kg, which is greater than the 170mAh / g - 3.3V of lithium iron phosphate in current kinetic batteries; 230mAh / g - 3.7V of ternary lithium. The actual energy density of sulfur has also reached 660Wh / kg, which is 2-3 times that of current commercial lithium-ion batteries. In addition, sulfur has the advantages of abundant reserves, low cost, and green environmental protection. It is most likely to replace lithium iron phosphate / ternary lithium material system and become the next generation of high-performance lithium-ion battery positive electrode material. However, sulfur has defects such as poor electrical conductivity, poor thermal conductivity, large volume expansion rate (>90%), low first efficiency (70.6%), low cycle life (only about 400 times), and "shuttle effect", making it impossible for single sulfur positive electrode materials to achieve large-scale market application.

[0004] In response to the above problems, first of all, researchers found that the expansion rate of sulfur when embedded by ions has a superposition effect of particle diameter expansion, that is, the volume expansion of sulfur particles is the accumulation and superposition of the volume expansion of all sulfur lattices in the particles. When ions are embedded in the sulfur lattice, the expansion of sulfur particles will be the superposition of the expansion of all sulfur lattices in the particles. The expansion rate of a single lattice is only the volume increase rate of ions embedded in the sulfur lattice (about 60%). So researchers thought of nano-sizing sulfur particles as small as possible. When sulfur is ground to 100nm, the expansion rate drops to 80%, and when it is 10nm, it drops to 60%, and the cycle life increases to 600 times. At this time, it is still not ideal as an electrode material. Secondly, researchers tried to build some holes in sulfur for ions, and added some guiding catalysts to allow ions to embed into holes instead of sulfur lattices. It was found in the experiment that the ion embedding induction characteristics of the sulfur lattice always take precedence over other embedding mechanisms, and most ions still preferentially embed into the sulfur lattice rather than the holes built for them. Researchers also considered sacrificing some material specific capacity to solve the problem of reducing sulfur expansion rate. The simple method is to mechanically mix sulfur and other elements (or materials) to form a composite positive electrode material. After comprehensive testing, researchers selected conductive carbon materials (such as conductive carbon black) as the composite object. The experiment found that the sulfur lattice still has the natural preferential ion embedding induction characteristics. When charging, the ions are still preferentially embedded in the sulfur lattice according to the sulfur-carbon ratio. After the sulfur lattice is full, it is embedded in the gaps between the carbon layers. The loss of specific capacity and the reduction of expansion rate are also basically carried out according to the sulfur-carbon ratio (for example, when the sulfur-carbon ratio is 95:5, the specific capacity of the composite material will be about 1200mAh / g, and the volume expansion rate will be about 80%; when it is 60:40, the specific capacity of the composite material will be about 1000mAh / g, and the volume expansion rate will be about 60%). Since 2010, researchers have developed a liquid fluidization method. Strictly speaking, the liquid fluidization method is a coating method. This method places carbon powder in a fluidized bed and adjusts the fluidized bed to make the carbon powder in a fluidized state. The elemental sulfur is liquefied and then atomized at a temperature of about 300°C. The atomized liquid sulfur is sprayed into a fluidized bed, and the atomized liquid sulfur is coated on the carbon powder material. After cooling, a sulfur-coated carbon sulfur-carbon composite material is obtained. Since the sulfur adheres to the surface of the composite particles, the volume expansion rate of the composite material is also consistent with that of nano-sulfur. This coating method is essentially to coat carbon with nano-sulfur. Although the electrical conductivity and thermal conductivity of the obtained composite positive electrode material are improved, the defect of volume expansion rate still exists. From the electron microscope, nano-sulfur adheres to the large-particle carbon core. The higher the sulfur ratio, the more nano-sulfur particles are coated on the carbon particles, and the more obvious the sulfur expansion of the material.

[0005] Therefore, it is urgent to develop a new modification method to overcome the defects of elemental sulfur itself and realize the large-scale market application of elemental sulfur positive electrode materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for modifying a battery carbon-sulfur positive electrode material using defect-free original graphene.

[0007] The purpose of the present invention is achieved by the following technical solution: a method for modifying a battery carbon-sulfur positive electrode material using defect-free original graphene, which comprises the following steps: S1. Primary coating: taking defect-free original graphene powder and sulfur powder, adding them into industrial pure alcohol or pure ether solution for dispersion and primary coating, and vacuum drying the obtained slurry to obtain graphene-modified and coated sulfur composite material powder, wherein the primary coating time is 6 to 24 hours; In this step, the mixed powder of graphene powder and sulfur powder is in a flowable paste in the container (with no stratification at rest as the standard). After one coating, the sulfur composite slurry modified and coated with graphene is first obtained. During the coating process, the graphene evenly fills the space between the sulfur powder particles, which can greatly improve the material's electrical conductivity, thermal conductivity, mechanical strength, reversible energy density, and sulfur-carbon affinity. During the vacuum drying process, the solvent of the sulfur composite slurry modified and coated with graphene evaporates, and the graphene remains dispersed.

[0008] S2. Secondary coating: The graphene-modified sulfur composite material powder, nano-carbon powder and modifier prepared in step S1 are added to a coating and modification machine, and the mixture is mixed and stirred at a speed of 2000 to 7000 r / min for 5 to 10 hours for secondary coating to obtain a graphene-modified carbon-coated sulfur composite cathode material powder; In this step, inorganic or organic compounds are used to coat the surface of the particles, which reduces the agglomeration of the particles. In addition, the coating generates a steric repulsion, which makes it difficult for the particles to re-agglomerate, which is beneficial to the improvement of material performance. In this step, the coating of the nano-carbon powder completes the birdcage structure, completely blocking the ion embedding into the sulfur lattice, and can further reduce the expansion of sulfur to 0. The coating also evenly fills the space between the sulfur powder particles. After secondary coating, a graphene-modified carbon-coated sulfur composite positive electrode material powder is obtained; S3. Post-processing: cold-pressing the graphene-modified carbon-coated sulfur composite cathode material powder into a briquette at room temperature, crushing the obtained briquette into powder, and obtaining the graphene-modified sulfur-carbon composite cathode material powder.

[0009] The cold pressing in this step increases the tap density of the material and thus increases the volume energy density of the material, and after crushing, a graphene-modified, coated sulfur-carbon composite positive electrode material powder with better performance is obtained.

[0010] As a preferred technical solution, the mass ratio of the defect-free original graphene powder and the sulfur powder is 1:600-950, and the volume ratio of the total mass of the defect-free original graphene powder and the sulfur powder to the industrial pure alcohol or pure ether solution is 1 mg:1 ml.

[0011] As a preferred technical solution, the primary coating in step S1 is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is ≥1500W.

[0012] As a preferred technical solution, the vacuum drying temperature in step S1 is 50-80° C., and the drying time is 10-15 hours.

[0013] As a preferred technical solution, in step S2, the mass ratio of the graphene-modified and coated sulfur composite material powder to the nano-carbon powder is 1.5-19:1, and the amount of the modifier added is 1% of the total mass of the graphene-modified and coated sulfur composite material powder and the nano-carbon powder.

[0014] As a preferred technical solution, the modifier is any one of sodium dodecylbenzoate, betaine, acrylamide, PEO, PPO or an inorganic dispersant. The modifier includes surfactants, hyperdispersants, inorganic substances and the like.

[0015] As a preferred technical solution, the pressure of the cold pressing in step S3 is 5 to 10 MPa.

[0016] As a preferred technical solution, the briquettes obtained in step S3 are crushed into powders with particle sizes of D10 = 5 μm and D50 = 15 μm using a dry ultrasonic jet airflow mill.

[0017] As a preferred technical solution, the particle size of the defect-free original graphene powder is 10 to 50 nm, the particle size of the sulfur powder is 1 to 10 μm, and the particle size of the nano-carbon powder is 50 to 100 nm.

[0018] The present invention uses nanocarbon as the coating material and micron sulfur powder as the core for coating. It successfully achieves "blocking ions from embedding into the sulfur lattice". The particle size of the sulfur core used in the present invention is 1 to 5 μm, the particle size of the carbon powder used is 50 to 100 nm, and the particle size of the graphene used is 10 to 50 nm. The more uniform and complete the coating layer is, the smaller the exposed sulfur surface area is, and the smaller the opportunity for ion embedding is. During charging, the ions can only be embedded in the interlayer gaps of sulfur and carbon, ultimately solving the problem of sulfur expansion. This is the birdcage structure used in chemical engineering. The birdcage coating structure is established with nanocarbon, which locks the sulfur particles in the cage and blocks the ions from embedding into the sulfur lattice.

[0019] At the same time, the present invention innovates secondary coating, and the coating materials are graphene as the first coating material and nano-carbon powder as the second coating material. The ultra-high mechanical strength of graphene is used to strengthen the birdcage structure, which not only effectively blocks the ion embedding into the sulfur lattice and suppresses the sulfur expansion rate, but more importantly, it can modify the positive electrode material to improve the material's electrical conductivity, thermal conductivity, fast charging performance, and safety performance. Graphene coating also improves the repellency of sulfur-carbon composites. Even if the sulfur particle size reaches the micron level, a dense sulfur-carbon structure can be formed. In an embodiment of the present invention, the tap density of the graphene-sulfur composite powder is greater than 0.92 g / cm 3 . Since graphene is expensive, the present invention mainly uses it for the purpose of modifying and strengthening the birdcage structure, and puts the task of blocking ions from embedding into the sulfur lattice on the secondary coated nano conductive carbon powder. After secondary coating in a continuous powder surface coating and modification machine with high-speed gas-solid phase vortex mixing, we only saw carbon under the electron microscope, while the sulfur particles had been completely coated and could not be seen. The coating effect was very obvious. There is currently no report on this coating effect. The test results show that the material expansion rate is close to 0, that is, the coated carbon-sulfur composite positive electrode material completely blocks the lithium ions from embedding into the sulfur lattice, solving the problem of sulfur expansion. The battery based on the embodiment of the present invention can have a reversible capacity greater than 950mAh / g even after 1500 cycles. In addition, the sulfur content in the nanocomposite material is preferably greater than about 70wt%. At present, no other domestic patents and technical documents have been found to have the same report.

[0020] It should be noted that the present invention does not use graphene oxide (GO), reduced graphene oxide (rGO) or their derivatives-sulfonated graphene to coat the carbon-sulfur cathode material. In the early stage of the cycle, the carbon-sulfur cathode prepared by coating with GO, rGO or sulfonated graphene has a greatly reduced intermolecular van der Waals force due to severe lattice distortion and electron hole defects, making it easier to be electrochemically wetted, which indicates that it is easier to disperse initially and easier to modify. Although the electrical performance of lithium-ion batteries in the early stage of modification is still far from that of real graphene, it improves the electrical performance of the cathode material after all. However, as the cycle continues to deepen, the nucleation overpotential of GO or rGO becomes gradually higher than that of defect-free original graphene, indicating that the Coulomb efficiency (CE) of the GO or rGO modified electrode begins to decline and accelerates, resulting in severe electrolyte interface (SEI) growth and related FEC consumption, and a large number of dendrites will be generated at the negative electrode after the cycle. The reason is that the structural defects of GO or rGO itself are integrated into the modified materials, causing a large number of structural defects in the modified materials, because highly defective GO or rGO will promote the growth of unstable SEI and form filamentous lithium dendrites at the negative electrode. The structural defects of GO or rGO modified materials will also lead to a continuous decline in battery electrical performance, and the resulting dendrites will bring major safety hazards of combustion and explosion. Another serious defect of GO or rGO is the residual defect of acid ions. No matter what method is used to wash GO and rGO, the acid ions in their molecules cannot be completely removed. Under certain environmental conditions, acid ions will precipitate from the materials modified by GO and rGO, and then corrode or poison the materials, and also produce a harmful environment to the human body in contact.

[0021] The present invention has the following advantages: The present invention discloses a method for modifying a battery carbon-sulfur positive electrode material with defect-free original graphene, wherein the method is to coat and modify the liquid / solid lithium-sulfur battery carbon-sulfur positive electrode material with defect-free original graphene, and complete the ion embedding lattice induced blocking of sulfur by nano-carbon secondary coating technology. Compared with the existing sulfur / sulfur-carbon positive electrode materials, the specific capacity of the graphene sulfur-carbon positive electrode material prepared by the method of the present invention is greatly increased and close to the theoretical value, and the electrical conductivity and thermal conductivity are greatly improved. The weight energy density and volume density of the liquid / solid lithium-sulfur battery prepared by the method are significantly increased, and the safety and reliability are far superior to the current lithium-sulfur batteries of the same type, which is very beneficial to the operation of the battery management system. The liquid / solid lithium-sulfur battery prepared by the method has a significant improvement in the number of charge and discharge cycles and life. The method of the present invention is simple to operate, convenient to prepare, and has a short production cycle, and is suitable for large-scale production. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with embodiments, and the protection scope of the present invention is not limited to the following: Embodiment 1: A method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene, comprising the following steps: S1. Primary coating: Take defect-free original graphene powder with a particle size of 30nm and sulfur powder with a particle size of 5μm, add them into industrial pure alcohol solution and use ultrasonic disperser for primary coating. The power of ultrasonic disperser is 1500W. The obtained slurry is vacuum dried at a temperature of 50°C for 15h to obtain graphene-modified and coated sulfur composite material powder; The time for one coating is 24 hours; the mass ratio of the defect-free original graphene powder to the sulfur powder is 1:600, and the volume ratio of the total mass of the defect-free original graphene powder and the sulfur powder to the industrial pure alcohol solution is 1 mg:1 ml; S2 secondary coating: The graphene-modified sulfur composite material powder obtained in step S1, 70nm nano-carbon powder, and sodium dodecylbenzoate modifier were added to the coating modification machine, and the mixture was mixed and stirred at a speed of 2000r / min for 10h for secondary coating to obtain a graphene-modified carbon-coated sulfur composite cathode material powder; The mass ratio of the graphene-modified and coated sulfur composite material powder to the nano-carbon powder is 1.5:1, and the amount of the modifier added is 1% of the total mass of the graphene-modified and coated sulfur composite material powder and the nano-carbon powder; S3. Post-processing: The graphene-modified carbon-coated sulfur composite cathode material powder is cold-pressed into a briquette at room temperature, the cold-pressing pressure is 5 MPa, and the obtained briquette is crushed into a powder with a particle size of D10 = 5 μm and D50 = 15 μm to obtain a graphene-modified sulfur-carbon composite cathode material powder.

[0023] Embodiment 2: A method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene, comprising the following steps: S1. Primary coating: Take defect-free original graphene powder with a particle size of 50 nm and sulfur powder with a particle size of 10 μm, add them into industrial pure ether solution and use an ultrasonic disperser for primary coating. The power of the ultrasonic disperser is 1800 W. The obtained slurry is vacuum dried at a temperature of 80° C. for 10 h to obtain a graphene-modified and coated sulfur composite material powder. The time for one coating is 6 hours; the mass ratio of the defect-free original graphene powder to the sulfur powder is 1:950, and the volume ratio of the total mass of the defect-free original graphene powder and the sulfur powder to the industrial pure ether solution is 1 mg:1 ml; S2 secondary coating: The graphene-modified sulfur composite material powder obtained in step S1, 50nm nano-carbon powder, and acrylamide modifier were added to the coating modification machine, mixed and stirred at a speed of 7000r / min for 5h for secondary coating to obtain a graphene-modified carbon-coated sulfur composite cathode material powder; The mass ratio of the graphene-modified and coated sulfur composite material powder to the nano-carbon powder is 19:1, and the amount of the modifier added is 1% of the total mass of the graphene-modified and coated sulfur composite material powder and the nano-carbon powder; S3. Post-processing: The graphene-modified carbon-coated sulfur composite cathode material powder is cold-pressed into a briquette at room temperature, the cold-pressing pressure is 10 MPa, and the obtained briquette is crushed into powder with a particle size of D10 = 5 μm and D50 = 15 μm to obtain a graphene-modified sulfur-carbon composite cathode material powder.

[0024] Embodiment 3: A method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene, comprising the following steps: S1. Primary coating: Take defect-free original graphene powder with a particle size of 10 nm and sulfur powder with a particle size of 1 μm, add them into industrial pure alcohol solution and use an ultrasonic disperser for primary coating. The power of the ultrasonic disperser is 2000 W. The obtained slurry is vacuum dried at a temperature of 65°C for 13 hours to obtain graphene-modified and coated sulfur composite material powder; The time for one coating is 15 hours; the mass ratio of the defect-free original graphene powder to the sulfur powder is 1:770, and the volume ratio of the total mass of the defect-free original graphene powder and the sulfur powder to the industrial pure alcohol solution is 1 mg:1 ml; S2 secondary coating: The graphene-modified sulfur composite material powder obtained in step S1, 100nm nano-carbon powder, and modifier PPO were added to the coating modification machine, mixed and stirred at a speed of 5000r / min for 8h for secondary coating to obtain a graphene-modified carbon-coated sulfur composite cathode material powder; The mass ratio of the graphene-modified and coated sulfur composite material powder to the nano-carbon powder is 8:1, and the amount of the modifier added is 1% of the total mass of the graphene-modified and coated sulfur composite material powder and the nano-carbon powder; S3. Post-processing: The graphene-modified carbon-coated sulfur composite cathode material powder is cold-pressed into a briquette at room temperature, the cold-pressing pressure is 7 MPa, and the obtained briquette is crushed into a powder with a particle size of D10 = 5 μm and D50 = 15 μm to obtain a graphene-modified sulfur-carbon composite cathode material powder.

[0025] The beneficial effects of the present invention are described below by experiments: 1. Experimental methods: Experimental Example 1-5 A method for modifying a carbon-sulfur cathode material of a battery using defect-free pristine graphene, comprising the following steps: S1. Primary coating: taking defect-free original graphene powder with a particle size of 10 nm and sulfur powder with a particle size of 10 μm, adding them to an industrial pure alcohol solution and using an ultrasonic disperser for primary coating, the power of the ultrasonic disperser is 1800 W, the primary coating time is 24 hours, the mixed powder is in a flowable paste state in the container (with no stratification at rest as the standard), and a graphene-modified and coated sulfur composite slurry is obtained, and the composite slurry is vacuum dried in a vacuum drying oven, the vacuum drying temperature is 60° C., and the drying time is 10 hours, to obtain a graphene-modified and coated sulfur composite material powder; S2. Secondary coating: The graphene-modified sulfur composite material powder obtained in step S1, 100nm nano-carbon powder, and betaine modifier were added to a continuous powder surface coating modifier, and the mixture was mixed and stirred at a speed of 4000r / min for 8h for secondary coating to obtain a uniform graphene-modified carbon-coated sulfur composite cathode material powder; S3. Post-processing: The graphene-modified carbon-coated sulfur composite positive electrode material powder is cold-pressed into a briquette at room temperature to increase the tap density of the material and thus increase the volume energy density of the material. The cold pressing pressure is 8 MPa. The obtained briquette is crushed in a dry ultrasonic jet airflow mill to a powder with a particle size of D10 = 5 μm and D50 = 15 μm to obtain a graphene-modified sulfur-carbon composite positive electrode material powder.

[0026] The raw material formula details of Experimental Examples 1-5 are shown in Table 1: Table 1: Raw material formula of Experimental Examples 1-5 2. Experimental results The relevant properties of the graphene-modified sulfur-carbon composite positive electrode material powders prepared in Experimental Examples 1-5 were tested, and the results are shown in Table 2: Table 2: Performance of graphene-modified sulfur-carbon composite cathode material powder samples This experiment found that: (1) When using an ultrasonic disperser to disperse graphene, the power cannot be less than 600W. The greater the power, the better the dispersion effect. When the power is greater than 1500W, the dispersion effect does not change much, so an ultrasonic separator with a power greater than 1500W can be selected; (2) Dry in a vacuum drying oven after one coating. If the drying temperature is low, the drying time will be long. The experiment chose to dry at 50℃~80℃ for 5~15 hours, but the temperature should not exceed 90℃ to avoid sulfur sublimation. After many experiments, the drying temperature was selected to be 60℃ and the drying time was 10 hours as the best; (3) In the secondary coating process of carbon powder, a continuous powder surface coating and modification machine with high-speed gas-solid vortex mixing is selected. The modification efficiency is high and the original particle shape of the powder is basically not destroyed. In terms of parameter selection, different combinations of sample points are coated and mixed at a speed of 2000-7000 rpm for 5-10 hours. The experiment showed that the coating time is short when the speed is high, but the coating is uneven when the speed is too high. The coating is more uniform when the coating time is long, but there is little change after the coating time exceeds 8 hours. After many experiments, 4000 rpm mixing and stirring for 8 hours was selected for secondary coating; (4) When implementing coating modification, if the size of the coating material is larger than the coated material (core), the coating material is prone to wrinkling, and thus the coating cannot be uniform and complete. The particle size of the core material should be at least 30 times larger than the particle size of the coating material to facilitate uniform coating of the coating material. The sample of the present invention is selected to be 30 to 50 times.

[0027] (5) When sulfur is used as the core coating object for coating modification, the sulfur-carbon ratio (mass ratio ranging from 60%:40% to 95%:5%) should be determined according to the application scenario of the graphene-modified carbon-coated sulfur composite positive electrode material. For example, if a harsh environment requires the electrode to have better electrical and thermal conductivity, a sulfur-carbon ratio of 60:40 can be selected, while a friendly environment requires the battery to have a better battery life, a sulfur-carbon ratio of 95:5 can be selected.

[0028] (6) Considering the limited battery space of household electric vehicles, in order to improve the volume energy density of the battery, the present invention adds a process for improving the material tap density, that is, the graphene-modified carbon-sulfur cathode material after secondary coating is cold-pressed (5-10 MPa) at room temperature and then crushed into the final product. The experiment found that the material tap density increased with the increase of cold pressing pressure, but after the pressure exceeded 8 MPa, the tap density no longer increased, so the cold pressing pressure was selected as 8 MPa in this experiment.

[0029] Through experiments, it is found that the performance of the sulfur-carbon composite positive electrode material powder modified and coated with graphene in the present invention is improved as follows: -The specific capacity is closer to the theoretical value of the material, which significantly increases the energy density of the corresponding ion battery; -The electrical conductivity and thermal conductivity are greatly improved, and the oxidation of the electrode surface is curbed. The electrical conductivity and thermal conductivity of the prepared liquid / solid lithium-sulfur battery are also greatly improved, and the energy density, safety, and reliability are all higher than the current lithium batteries of the same type and model, which is very beneficial to the operation of various battery management systems; -The initial efficiency of liquid / solid lithium-sulfur batteries prepared by it can reach more than 90%; -The liquid / solid lithium-sulfur batteries prepared using it have significantly improved the number of charge and discharge cycles and lifespan; -The solid-state lithium-sulfur battery prepared by it can be fast-charged up to 6C to 12C without damaging the internal structure, and is compatible with the 800V charging platform currently recommended in the world.

[0030] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.

Claims

1. A method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene, characterized in that: It includes the following steps: S1. Primary coating: taking defect-free original graphene powder and sulfur powder, adding them into industrial pure alcohol or pure ether solution for dispersion and primary coating, and vacuum drying the obtained slurry to obtain graphene-modified and coated sulfur composite material powder, wherein the primary coating time is 6 to 24 hours; S2. Secondary coating: The graphene-modified sulfur composite material powder, nano-carbon powder and modifier prepared in step S1 are added to a coating and modification machine, and the mixture is mixed and stirred at a speed of 2000 to 7000 r / min for 5 to 10 hours for secondary coating to obtain a graphene-modified carbon-coated sulfur composite cathode material powder; S3. Post-processing: cold-pressing the graphene-modified carbon-coated sulfur composite cathode material powder into a briquette at room temperature, crushing the obtained briquette into powder, and obtaining the graphene-modified sulfur-carbon composite cathode material powder.

2. The method for modifying a carbon-sulfur cathode material of a battery using defect-free pristine graphene according to claim 1, characterized in that: The mass ratio of the defect-free original graphene powder to the sulfur powder is 1:600-950, and the volume ratio of the total mass of the defect-free original graphene powder and the sulfur powder to the industrial pure alcohol or pure ether solution is 1 mg:1 ml.

3. The method for modifying a carbon-sulfur cathode material of a battery using defect-free pristine graphene according to claim 1, characterized in that: The primary coating in step S1 is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is ≥1500W.

4. The method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene according to claim 1, characterized in that: The vacuum drying temperature in step S1 is 50-80° C., and the drying time is 10-15 hours.

5. The method for modifying a carbon-sulfur cathode material of a battery using defect-free pristine graphene according to claim 1, characterized in that: In step S2, the mass ratio of the graphene-modified and coated sulfur composite material powder to the nano-carbon powder is 1.5-19:1, and the amount of the modifier added is 1% of the total mass of the graphene-modified and coated sulfur composite material powder and the nano-carbon powder.

6. The method for modifying a battery carbon-sulfur cathode material using defect-free pristine graphene according to claim 1, characterized in that: The modifier is any one of sodium dodecylbenzoate, betaine, acrylamide, PEO, PPO or an inorganic dispersant.

7. The method for modifying battery carbon-sulfur cathode material using defect-free pristine graphene according to claim 1, characterized in that: The pressure of the cold pressing in step S3 is 5-10 MPa.

8. The method of modifying battery carbon-sulfur cathode material using defect-free pristine graphene according to claim 1, characterized in that: The briquette obtained in step S3 is crushed into powder with a particle size of D10 = 5 μm and D50 = 15 μm using a dry ultrasonic jet airflow mill.

9. The method of modifying battery carbon-sulfur cathode material using defect-free pristine graphene according to claim 1, characterized in that: The particle size of the defect-free original graphene powder is 10-50 nm, the particle size of the sulfur powder is 1-10 μm, and the particle size of the nano carbon powder is 50-100 nm.